DIRECTIONS OF TEACHER-STUDENT COOPERATION - Karimli, Nusiya; Rzayeva, Jale (Revista Gênero e Interdisciplinaridade, 2025)
This article examines the importance of teacher-student cooperation in the educational process and its various aspects. Teacher-student cooperation is not only about transferring knowledge, but also about the personal development of students, the development of creative thinking skills, and social responsibilities. The article emphasizes that education is not just about providing information, and highlights the role of teachers in actively communicating with students, shaping their way of thinking, arousing motivation and interest, and strengthening students’ independent thinking and creative problem-solving skills. The article also highlights the importance of teachers’ continuous self-development. Various aspects of teacher-student cooperation are important factors that stimulate the development of both parties. This cooperation serves the positive development of both teachers and students and forms an educational environment that will guide the future of society.